Probing the Intramolecular Metal‐Selenoether Interaction in a Bis(iminosemiquinone)copper(II) Compound. Issue 21 (20th October 2017) - Bubrin, Martina; Paretzki, Alexa; Hübner, Ralph; Beyer, Katharina; Schwederski, Brigitte; Neugebauer, Petr; Záliš, Stanislav; Kaim, Wolfgang
Abstract : The selenoether compound [Cu(QSeMe )2 ] [H2 QSeMe = 4, 6‐di‐ tert ‐butyl‐2‐(2‐methylselenophenyl)aminophenol] exhibits solvate‐dependent NCuO/OCuN twisting (24° and 33°) and very weak copper–chalcogen interactions (3.30–3.55 Å) in the crystal. Structural studies as well as EPR and magnetic measurements confirm a bis(iminosemiquinone)copper(II) configuration with one ligand‐based spin in the S = ½ ground state. A spin up‐down‐up sequence is thus inferred for the (Q – )–Cu II –(Q – ) three‐spin system. UV/Vis/NIR spectroelectrochemistry in CH2 Cl2 /0.1 M Bu4 NPF6 reveals a broad ligand‐to‐ligand intervalence charge transfer (Q 2– → Q – ) band at 1910 nm for the monoanion whereas the stepwise two‐electron oxidation leads to loss of intensity in the near infrared region. DFT calculations of structure, spin density, and electronic transitions were performed to confirm the assignments of oxidation states and absorption features. Abstract :